PENGARUH PERAN GANDA, FLEKSIBILITAS JAM KERJA DAN UPAH TERADAP PRODUKTIVITAS KERJA PADA PT. HOLI KARYA SAKTI SEMARANG (STUDI KASUS PADA BURUH PEREMPUAN BAGIAN PRODUKSI) - Oktya Deffi Antiqka; Ari Pradhanawati (Universitas Diponegoro, 2017)
Labor productivity is an important thing that must be considered and often used to measure the extent to which workers can reach the target set company .Labor productivity can be influenced by several factors among them are the dual role , flexibility of working hours , and wages . PT .Holi Karya Sakti Semarang is the company garment that develops with the production and export gloves golf and sky .The purpose of this research is to know the influence of the dual role , flexibility of working hours , and wages against labor productivity on PT. Holi Holi Karya Sakti Semarang. This research using a quantitative approach .Sample 100 laborers a number of women who are married and have a child using random sampling technique. Data collection use instruments the questionnaire.Analysis research on the SPSS 20.0 version. The result showed that the dual role influences work productivity with t count 1,742 > t table 1,661. Flexibility working hours influences work productivity with t count 1,705 > t table 1,661.Wages influences work productivity with t count 2,452 > t table 1,661. Simultaneously the dual role, flexibility working hours, and wages influences work productivity with an f count 3,549 & gt; f table 2,14 with the significance 0,000 > 0,010.Advice for companies to support the dual role by workers women, increase the flexibility working hours and increase their salaries considered less appropriate.Third the variables have some indicator less than optimal so as to can increase productivity work can be be done by improving the dual role, flexibility working hours and wages